2001
DOI: 10.1210/endo.142.8.8333
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Independent Activation of Pituitary ER: Dependence on PKA-Stimulated Pathways

Abstract: In pituitary and other target tissues, estrogen acts through ERs, which are ligand-activated nuclear transcription factors. ERs can also be activated by intracellular signaling pathways in a ligand-independent manner in some cells. Because the pituitary is the target of several cAMP-activating factors, we examined the ability of cAMP to activate ERs in the alphaT3 gonadotrope cell line. Forskolin, 8-bromo-cAMP, and pituitary adenylate cyclase-activating polypeptide all enhanced ER-dependent promoter activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…As shown in Fig. 1a, non-radiolabelled E 2 , ICI182,780 and TAM efficiently competed with [ 3 H]17␤-estradiol for specific binding to ERs present in cytosol preparations from L-(hFSHR − ) cells (IC 50 16 ± 0.10, 21 ± 0.13 and 15 ± 0.09 nM, for E 2 , ICI182,780 and TAM, respectively), whereas increasing concentrations of the synthetic progestin norethisterone was unable to displace [ 3 H]17␤-estradiol from the receptor. The presence of both ER␣ and ER␤ in these cells was confirmed by immunocytochemical studies (Fig.…”
Section: Estradiol and Fsh Induce Transcriptional Activation Of The 3mentioning
confidence: 88%
See 1 more Smart Citation
“…As shown in Fig. 1a, non-radiolabelled E 2 , ICI182,780 and TAM efficiently competed with [ 3 H]17␤-estradiol for specific binding to ERs present in cytosol preparations from L-(hFSHR − ) cells (IC 50 16 ± 0.10, 21 ± 0.13 and 15 ± 0.09 nM, for E 2 , ICI182,780 and TAM, respectively), whereas increasing concentrations of the synthetic progestin norethisterone was unable to displace [ 3 H]17␤-estradiol from the receptor. The presence of both ER␣ and ER␤ in these cells was confirmed by immunocytochemical studies (Fig.…”
Section: Estradiol and Fsh Induce Transcriptional Activation Of The 3mentioning
confidence: 88%
“…Estrogen receptor activation modulates transcription of specific genes by engaging a number of transcription factors (co-activators or co-repressors) in target cells, which in turn negatively or positively regulate transcriptional activity of ligand-activated receptors [7,8] In addition to estrogen-mediated activation, the transcriptional effects of ERs can be mediated through several mechanisms other than estradiol (E 2 )-ER complexes binding to DNA [9,10]. It is now accepted that ERs may be activated in the absence of E 2 by a variety of extracellular signals, including growth factors [11][12][13] and other cell surface membrane-targetted signals that trigger activation of a number of kinase-regulated signaling cascades including the cAMP/protein kinase A (PKA) pathway [12,[14][15][16][17], protein kinase C (PKC) [14,18,19], phosphatidylinositol 3 (PI3)-dependent kinase (PI3-K)/Akt [20,21], and mitogenactivated protein kinase (MAPK) pathways [11,[22][23][24]. Selective expression of receptors for these ligands, along with differences in ER isoform and coactivator/corepressor protein expression allow for target cell-and promoter-specific effects of activated ERs [6,8,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of PKA in ER phosphorylation remains controversial and cannot explain the enhancement of transcription by itself. While some researchers claim that a contribution could also be due to phosphorylation of SRC-1 by PKA on the amino acid residues T1179 and S1185 [126], others state that the co-activator SRC-1 cannot be phosphorylated directly by PKA [127]. Recent evidence suggests that phosphorylation of ER-S305, within the D-Domain of ERa, leads to an altered orientation between ER and its co-activator SRC-1.…”
Section: Non-genomic Estrogen Signalingmentioning
confidence: 99%
“…These findings indicate that growth factors exert their actions through the ER. Indeed, a number of studies using ERE-containing promoter-driven reporter genes have shown ligand-independent ERE-mediated transcriptional activation in a variety of cell lines in response to EGF [9][10][11][12], transforming growth factor (TGF)-␣ [9,12], insulin-like growth factor-1 (IGF-1) [9,[12][13][14], insulin [13][14][15], heregulin [16], cAMP [10,11,17], dopamine [10,18,19], and tetradecanoyl 12-phorbol 13-acetate [12]. The physiological and pathological significance of ligand-independent ER activation, however, remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…We developed an adenovirus-mediated, Cre/loxP-based, lactotrophspecific, ER transcriptional assay, which we named LASETA. This assay specifically targeted the lactotrophs within a primary culture of pituitary cells which also contains estrogen-responsive gonadotrophs suggested to exhibit ligand-independent ER activation in response to cAMP administration [17]. The Cre/loxP system was used to restrict the luciferase reporter gene expression to lactotrophs by regulating the expression of Cre recombinase by PRL promoter activity.…”
Section: Introductionmentioning
confidence: 99%